90Y/177Lu‐labelled Cetuximab immunoconjugates: radiochemistry optimization to clinical dose formulation. (5th June 2016) - Chakravarty, Rubel; Chakraborty, Sudipta; Sarma, Haladhar Dev; Nair, K. V. Vimalnath; Rajeswari, Ardhi; Dash, Ashutosh
Abstract : Radiolabelled monoclonal antibodies (mAbs) are increasingly being utilized in cancer theranostics, which is a significant move toward tailored treatment for individual patients. Cetuximab is a recombinant, human–mouse chimeric IgG1 mAb that binds to the epidermal growth factor receptor with high affinity. We have optimized a protocol for formulation of clinically relevant doses (~2.22 GBq) of 90 Y‐labelled Cetuximab and 177 Lu‐labelled Cetuximab by conjugation of the mAb with a suitable bifunctional chelator, N‐[(R)‐2‐amino‐3‐(paraisothiocyanato‐phenyl)propyl]‐trans‐(S, S)‐cyclohexane‐1, 2‐diamine‐N, N, N′, N″, N″‐pentaacetic acid (CHX‐A″‐DTPA). The radioimmunoconjugates demonstrated reasonably high specific activity (1.26 ± 0.27 GBq/mg for 90 Y‐CHX‐A″‐DTPA‐Cetuximab and 1.14 ± 0.15 GBq/mg for 177 Lu‐CHX‐A″‐DTPA‐Cetuximab), high radiochemical purity (>95%) and appreciable in vitro stability under physiological conditions. Preliminary biodistribution studies with both 90 Y‐CHX‐A″‐DTPA‐Cetuximab and 177 Lu‐CHX‐A″‐DTPA‐Cetuximab in Swiss mice bearing fibrosarcoma tumours demonstrated significant tumour uptake at 24‐h post‐injection (p.i.) (~16%ID/g) with good tumour‐to‐background contrast. The results of the biodistribution studies were further corroborated by ex vivo Cerenkov luminescence imaging after administration of 90 Y‐CHX‐A″‐DTPA‐Cetuximab in tumour‐bearing mice. The tumour uptake at 24 h p.i. was significantly reduced with excess unlabelled Cetuximab, suggesting that the uptake was receptor mediated. The results of this study hold promise, and this strategy should be further explored for clinical translation. Abstract : A procedure has been optimized for preparation of clinically relevant doses of 90Y‐labelled and 177Lu‐labelled Cetuximab immunoconjugates for potential use in cancer theranostics. The biological efficacy of the radiolabelled agents was established by biodistribution studies in Swiss mice bearing fibrosarcoma tumours, which was further substantiated by Cerenkov luminescence imaging (CLI).